Factors that affect consumer buying behavior towards online shopping - Jesika Marie T. Camacho, Alfredo Raymond B. Mahinan III, Jessica M. Ranin and Jonn Criztoriel E. Ventura. 4 0 16; 5
u
Undergraduate Thesis: (Bachelor of Science in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2